CHANGES IN ORAL CAVITY IN ENDOCRINE DISEASES - Sodiqova Shoira Amriddinovna; Axrorov Ixlosjon; Ziyodullayeva Muhabbat; Yunusova Dinora (Journals Park Publishing, 2023)
The oral cavity serves as a diagnostic window to systemic health, and its manifestations often provide vital clues to underlying medical conditions. One intriguing area of study is the impact of endocrine diseases on oral health. Endocrine diseases, characterized by hormonal imbalances, can lead to a wide range of oral manifestations and complications. In this comprehensive article, we explore the intricate relationship between endocrine disorders and changes in the oral cavity. We delve into the pathophysiological mechanisms, clinical presentations, diagnosis, and management of these oral manifestations, shedding light on how healthcare professionals can better understand and address these issues.
Keywords: Endocrine diseases, Oral cavity, Oral health, Diabetes mellitus, Thyroid disorders, Adrenal disorders, Gonadal disorders, Parathyroid disorders, Pituitary disorders, Periodontal disease, Xerostomia, Oral candidiasis, Cushing's syndrome, Addison's disease, Polycystic ovary syndrome, Hypogonadism, Acromegaly, Dental health, Hormonal imbalances.